Fabrication and thermal performance of grooved-sintered wick heat pipe - Jiang, Le-lun; Tang, Yong; Wu, Hui-yue; Zhou, Wei; Jiang, Lin-zhen (Journal of Central South University, 2014)
Some novel grooved-sintered composite wick heat pipes (GSHP) were developed for the electronic device cooling. The grooved-sintered wicks of GSHP were fabricated by the processes of oil-filled high-speed spin forming and solid state sintering. The wick could be divided into two parts for liquid capillary pumping flow: groove sintered zone and uniform sintered zone. Both of the thermal resistance network model and the maximum heat transfer capability model of GSHP were built. Compared with the theoretical values, the heat transfer limit and thermal resistance of GSHP were measured from three aspects: copper powder size, wick thickness and number of micro grooves. The results show that the wick thickness has the greatest effect on the thermal resistance of GSHP while the copper powder size has the most important influence on the heat transfer limit. Given certain copper powder size and wick thickness, the thermal resistance of GSHP can be the lowest when micro-groove number is about 55.